1975
DOI: 10.1111/j.1600-0404.1975.tb05823.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Limits of Tolerance in Repeated Subarachnoid Hemorrhage in Dogs

Abstract: The effects of repeated subarachnoid hemorrhages have been investigated experimentally in dogs. The main objectives were to determine the tolerance to repeated hemorrhage and to study the changes occurring during the repeated bleeds, in intracranial pressure, EEG, ECG, systemic arterial pressure and respiration. The natural course of an intracranial hemorrhage was simulated by shunting blood from a femoral artery through a drop recorder into five different sites in the craniospinal system: the chiasmatic ciste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
5

Year Published

1976
1976
2007
2007

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 13 publications
1
27
0
5
Order By: Relevance
“…Brain homeostasis. Autoregulation of cerebral blood flow, increased oxygen extraction and the inherent tolerance of cerebral tissue to ischaemia in intracranial hypertension, together contribute to survival of brain tissue during the period of intracranial hypertension33, 62,67,68,85,86 3. Intact coagulation system.…”
Section: Introductionmentioning
confidence: 99%
“…Brain homeostasis. Autoregulation of cerebral blood flow, increased oxygen extraction and the inherent tolerance of cerebral tissue to ischaemia in intracranial hypertension, together contribute to survival of brain tissue during the period of intracranial hypertension33, 62,67,68,85,86 3. Intact coagulation system.…”
Section: Introductionmentioning
confidence: 99%
“…2. Brain homeostasis, integrating several mechanisms (autoregulation of the cerebral blood flow and increased cerebral oxygen extraction; ischemia tolerance of the brain tissue which facilitates brain survival during the period of intracranial hypertension 11,18,[17][18][19][20]. 3.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical deterioration may be explained by progressive intracerebral expansion in both patients. The total volume of intracerebral contusions and epidural haematomas (which were classified as large) might together have exceeded the critical volume threshold for clinical deterioration to appear ~5~, 72,74 A fracture was found in 29 out of 35 patients. It was present in all patients with verified shunts, and only in half of those who had none.…”
Section: Discussionmentioning
confidence: 97%
“…This pattern is usually followed irrespective of the origin, anatomical site, or the size of the bleeding source 56. [71][72][73][74] Studies by other authors on experimentally-induced epidural bleeds in dogs have suggested that they behave in a similar way 20 Clinical data from patients with epidural bleeds appear, however, to contradict the experimental results 1 3, 5, 7--10, 14 15, 18, 21, 26, 29, 30, 31, ~5, ~8, 40, 4~, 44, 45, 58 60, 61, 63, 65, 76 Thus the classical "latent interval" is easier to explain if one assumes the bleed to be longlasting, starting at the moment of trauma, progressing continuously, and causing clinical symptoms at a later stage. The demonstration of extravasation of contrast medium from lacerated meningeal vessels many days after trauma has also been regarded as being in favour of long-lasting bleeding.…”
Section: Introductionmentioning
confidence: 99%